2018
DOI: 10.1080/15140326.2018.1526877
|View full text |Cite
|
Sign up to set email alerts
|

Inflation targeting and inflation deviation inertia: a study for Brazil based on the fractional integration approach

Abstract: We applied the fractional integration approach to measure inflation deviation inertia in an emerging economy under an inflation targeting regime, as well as to control for potential determinants of such a deviation. We did not base our analysis on typical unit root tests, as we identified a long-memory behavior in inflation deviation. Such a non-conventional procedure can be regarded as a contribution to the inflation targeting literature. From ARFIMA and ARFIMAX estimates, we identified that inflation deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In turn, we allowed for an inertial inflationary component (0.8 for 𝑏 𝑝𝑡−1,𝑝 ), i.e., an effect of the lagged inflation rate on the current level. Such a parameter was built on the findings of Moreira et al (2018). At last, we also included a smoothing component into the interest rate dynamics, following the adopted central value (0.9 for 𝑏 𝑟𝑡−1,𝑟 ) in the structural model of the Brazilian Central Bank (Central Bank of Brazil, 2020).…”
Section: A Robustness Checking: a Calibrated Svarmentioning
confidence: 99%
“…In turn, we allowed for an inertial inflationary component (0.8 for 𝑏 𝑝𝑡−1,𝑝 ), i.e., an effect of the lagged inflation rate on the current level. Such a parameter was built on the findings of Moreira et al (2018). At last, we also included a smoothing component into the interest rate dynamics, following the adopted central value (0.9 for 𝑏 𝑟𝑡−1,𝑟 ) in the structural model of the Brazilian Central Bank (Central Bank of Brazil, 2020).…”
Section: A Robustness Checking: a Calibrated Svarmentioning
confidence: 99%
“…Diaz-Roldan, Ferrari-Filho, and da Silva Bichara (2019) showed that adoption of a adequate fiscal policy rule leads to rationalizing fiscal consolidation with IT. Moreira, Monte, and Abdala (2018) found that inflation deviation from the target level in Brazil was determined by commodity prices, nominal exchange rate, and economic performance.…”
Section: It Policymentioning
confidence: 99%